Photorelease of amino acids from novel thioxobenzo[f]benzopyran ester conjugates - Piloto, Ana M. (2012)
Aiming at the enhancement of the performance of (9-methoxy-3-oxo-3H-benzo[f]benzopyran-1-yl) methyl ester as photocleavable protecting group for the carboxylic acid function at long-wavelengths, 9-methoxy-3-thioxo-3H-benzo[f]benzopyran-L-valine and L-phenylalanine model conjugates were prepared through a thionation reaction of the corresponding oxo-benzobenzopyrans. These thioxobenzobenzopyran derivatives were subjected to photocleavage reactions in the same conditions as the parent oxo-benzobenzopyrans at different wavelengths of irradiation, and photocleavage kinetic data was obtained. It was found that the exchange of the carbonyl by a thiocarbonyl group enhanced the performance of the heterocyclic protecting group at 419 nm by improving the photolysis rates, making it an appropriate group for practical applications at long wavelengths.